Semiotika Fraud di Badan Amil Zakat Nasional (BAZNAS) Daerah - Hanif, Padlim (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2023)
Zakat is an instrument that can be a blessing for the universe. Through Zakat, justice and social order are very possible to be realized. Zakat management through Badan Amil Zakat Nasional (BAZNAS) Daerah is one phenomenon that is always interesting to study continuously. Even the phenomenon of Zakat management also experiences various dynamics, both positive and negative. As one of the dynamics that occurs, among others, is the occurrence of fraud in the management of Zakat by certain officials of Badan Amil Zakat Nasional (BAZNAS) Daerah. Of course, this is a very serious blow to the sanctity of the noble values contained in Zakat. Therefore, it is necessary to find out why this can happen. Because even though Badan Amil Zakat Nasional (BAZNAS) Daerah is a non-profit institution, it does not mean that it is not a must to pay attention to its management. In fact, the management of Zakat funds should be supervised more optimally. Just as funds in the banking business can be supervised properly and correctly, it is not impossible that the same treatment can also be applied to Zakat Funds. Given that the existence of Zakat Funds is related to many interested parties who have the right to receive and are obliged to give.